2014
DOI: 10.1159/000360794
|View full text |Cite
|
Sign up to set email alerts
|

Loss of E-Cadherin Expression Is Associated with a Poor Prognosis in Stage III Colorectal Cancer

Abstract: Purpose: The epithelial-mesenchymal transition (EMT) is known to be associated with tumor progression, invasion and metastasis in colorectal cancer (CRC). Materials and Methods: Tissue samples obtained from 409 patients with stage III CRC treated from 2006 to 2007 were examined by immunohistochemistry to reveal the expression levels of E-cadherin, fibronectin, vimentin and α-smooth muscle actin (SMA). Results: Among the 409 patients, 402 cases (98.3%) showed positive E-cadherin expression. Positive E-cadherin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 18 publications
2
37
1
Order By: Relevance
“…In CRCs, PAICS is involved in regulating the EMT, which is involved in regulation of cancer cell invasion and metastasis [44]. In CRCs, the loss of E-cadherin and gain of vimentin are implicated in cancer progression, and metastasis and are associated with a poor prognosis [45]. A previous study showed that the histone methyltransferase, EZH2, mediates transcriptional silencing of E-cadherin by trimethylation of H3 lysine 27 [46].…”
Section: Discussionmentioning
confidence: 99%
“…In CRCs, PAICS is involved in regulating the EMT, which is involved in regulation of cancer cell invasion and metastasis [44]. In CRCs, the loss of E-cadherin and gain of vimentin are implicated in cancer progression, and metastasis and are associated with a poor prognosis [45]. A previous study showed that the histone methyltransferase, EZH2, mediates transcriptional silencing of E-cadherin by trimethylation of H3 lysine 27 [46].…”
Section: Discussionmentioning
confidence: 99%
“…invasion. E-cadherin loss is an integral step in the epithelial-mesenchymal transition (EMT), that is associated with tumor progression, invasion and metastasis in CRC (Heerboth et al 2015;Yun et al 2014). Conversely, increased E-cadherin expression has been shown to decrease ERK1/2 phosphorylation, suggesting a suppressor role in the Kras oncogenic pathway (Satow et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…22 Furthermore, intermediate filaments are shown to switch from cytokeratin to vimentin during EMT and increased vimentin levels are also a consistent marker during various EMT events. 23 In recent years, some of the metastatic actions of WAVE3 could be explained by its role in epithelial mesenchymal transition. Here, we showed that upregulating WAVE3 in SGC-7901 cells by pcDNA3.1-WAVE3 led to reduced expression of E-cadherin, and increased expression of vimentin.…”
Section: Discussionmentioning
confidence: 99%